How did Feldstein (1985) undervalue the optimal level of social security benefits? - András Simonovits (Hungarian Academy of Sciences, Institute of Economics, 2017)
In his seminal model (Feldstein, 1985), the government operates a social security system to counter the representative worker's myopia. (i) For a complete myope, he determined a sizable optimal tax rate (and the corresponding benefit level). (ii) For a partially shortsighted worker, he determined another optimum, which was much lower, possibly zero. Departing from Feldstein, I take into account that neither a paternalistic government nor a cautious bank tolerates long-term negative saving, and then even in (ii), the government may choose the first rather than the second optimum. Having revised it, Feldstein's model regains its place in the textbooks.
Keywords: D10; H55; J13; J14; J18; J26; 330; social security; myopia; paternalism; social welfare